(untitled) (Pulse, 2016)
Molecular diagnosis is rapidly becoming an inseparable part of disease diagnosis. This cutting edge technology can be used to diagnose both infectious and malignant diseases as well as to help in determining drug dosage, tissue types for organ transplant and risk of inherent disorders. An added advantage is that it provides an indication of therapeutic choice, therapy response and disease prognosis. A survey was conducted among diagnostic laboratories and research institutes of Bangladesh to observe the existing range of molecular diagnostic tests in Bangladesh. It is found that though molecular tests started in diagnostics about 15 years before, range of tests is still very limited in the country. Challenges faced in establishing as well as sustaining these tests were noted and opinions recorded from stakeholders regarding further opportunities to improve this area. We found that challenges are limited knowledge on molecular tests among physicians, unfavorable custom regulations and inadequate after-sale support from suppliers, cost of the tests and strong advocacy and marketing strategies of neighboring countries. To overcome these challenges our recommendations are inclusion of molecular medicine in medical curriculum, dissemination of information about molecular tests to existing physician community, minimum custom duty and minimum profit margin by the stakeholders to reduce test price. In addition, review of policies regarding import and support of cutting edge technology in diagnostic sector with involvement of available experts in this field is essential to make this valuable sector viable. Pulse Vol.8 January-December 2015 p.51-61